Between Stuff Happens and Ishtar in Baghdad: Justifications and Results of American War on Iraq - Jassim, Jinan Waheed (Al-Adab Journal, 2019)
Theatre was and still is one of the pioneer literary genres in recording and presenting history, past and present. It is a tool and a means utilized by playwrights-intellectuals to document real life events, in addition to its role in entertaining and producing fictional literature. As a part of its enlightening mission, drama served as a lively method in presenting the truth to the public, a truth that might be hidden or twisted by media, news broadcasts, or public speeches in accordance with certain political agendas. In this sense theatre played a great role in dramatizing the American-led war against Iraq in 2003. Many plays tackled the events and incidents related to this war. Among those plays are David Hare’s Stuff Happens and Rasha Fadhil’s Ishtar in Baghdad. When the British playwright dramatizes the events leading to waging a coalition war on Iraq in his documentary play, the Iraqi dramatist conveys a grim picture of the country in the aftermath of that war, mixing images of the mythical golden history of Iraq with its most recent images of destruction and chaos, yet giving hope in a brighter and more peaceful future.